Granular Cell Tumor Confined To The Muscularis Propria Of The Appendix: A Case Report. (28th October 2020) - Allison, D; Rao, D
Abstract: Introduction/Objective: Granular cell tumors (GCTs) are exceedingly rare soft tissue tumors that are usually benign and are thought to arise from Schwann cell origin. GCTs most commonly occur in the skin, subcutaneous tissue, and oral cavity. However, they can involve any organ, including the gastrointestinal (GI) tract, of which esophagus is most common, followed by large intestine. We report a case of a 58 year old female who presented with acute appendicitis, followed by an appendectomy to reveal an incidental GCT. Methods: This report is a retrospective study of an appendiceal GCT in which we reviewed the case and the histology. In addition, a brief literature review of gastrointestinal GCTs was performed to further elucidate the incidence, location, histopathology, and differential diagnoses for this lesion. Results: Histological analysis of the tumor nodule reveals nests of epithelioid cells with abundant granular eosinophilic cytoplasm. The nuclei are bland, small, and round to oval, with rare spindled morphology. Immunohistochemistry for S-100 protein shows diffuse strong cytoplasmic and nuclear positivity, which is suggestive of Schwann cell origin. In the GI tract, GCTs are routinely confined to the mucosa, submucosa, or both; however the tumor nodule in our case is contained within the muscularis propria. Conclusion: It is estimated that 5–11% of GCTs occur in the gastrointestinal tract, while only 13 GCT cases of the appendix have been reported. In addition to the previously stated rarity, is the limited involvement of the muscularis propria, with which GCTs typically are not associated. To our knowledge, this is the first confirmed GCT of the appendix that solely involves the muscularis propria, in English medical literature.